Art as Language : Wittgenstein, Meaning, and Aesthetic Theory - Hagberg, Garry, 1952- (Book collections on Project MUSE., 1995)
Focusing on the work of Arthur Danto, George Dickie, and Joseph Margolis, Hagberg discusses the philosophical presumptions and hidden complexities in recent theories of artistic perception, in theories concerning the nature of the art object, and in the institutional conception of the arts. Throughout Art as Language, he tests the claims of aesthetics against artistic practices in order to rethink the fundamental positions of the most important aesthetic theories of this century.